PKM USAHA AIR SUSU KEDELAI UNTUK HOME INDUSTRY - Masdani Masdani; Ariyanto Ariyanto (Jurnal Pengabdian Masyarakat Polmanbabel, 2021)
Soy milk is obtained by grinding soybeans soaked in water. In producing soy milk, Mitra experienced problems because the equipment in the production process was still manual and very simple. So that the production time becomes long and has an impact on the lack of income due to the limited production equipment. The aim of this community service program is to assist household-scale soy milk producer partners in terms of improving the quantity and quality of soy milk products. The solution that we can do through this program is by providing and introducing a soy milk machine and explaining how to maintain the machine. Results or output targets achieved from community service for partners, namely partners have used soy milk production machines so that the quality and quantity of soy milk can increase. In addition, there is an increase in the number of customers and turnover of partners as well as an increase in understanding and skills of partners.